Kondisi Sinyal R Gelombang QRS Jantung Dalam Rangka Mitigasi Pandemi - pramuyanti, roni kartika (ReTII, 2022)
The R signal as part of the heart’s QRS wave has physical and clinical significance to a person’s condition. The R signal is the highest signal or the amplitude for the cardiac QRS waves. As the highest wave of the R signal, of course, it has several specifications that must be met, including the lowest or highest signal height, the width or fatness of the R signal itself must also have a certain value and the presence of interference or other signals that have the R signal. After knowing some of these specifications, it will be able to classify the group from the R signal or QRS wave of the heart or even to health problems or disorders that occur in the owner of the heart. Apart from heart problems or health problems in humans, it can also be seen the common causes of the heart QRS wave R signal disturbance. Keywords: R signal, Cardiac QRS wave, Amplitude, Specification, Classification